Turista 2.0, comportamiento y uso de los medios sociales. - ALTAMIRANO BENÍTEZ, Verónica; TÚÑEZ LÓPEZ, Miguel; MARÍN GUTIÉRREZ, Isidro (Chasqui (13901079))
When referring to tourism activity we study experiences and the use of social media allowing tourists 2.0 to have a first approach to their destination, generating a foregoing experience that motivates and influences the selection process. This research reviewed, from 2012 to 2016, the behavior of tourist 2.0 at the official digital platforms of tourism from 22 Ibero-American countries; in that direction is oriented an analysis of almost 150 million online interactions in order to identify their interests, tastes, and identify trends of participation in their social media.